Fragmentation Typology of Sumatran Tropical Lowland Forest, Labuhanbatu Selatan - Indonesia - Samsuri; Febrianti Sitorus; Anita Zaitunah; Alfan Gunawan Ahmad (Research Centre of Inorganic Materials and Complexs, 2021)
Forest land cover experienced changes caused by various factors. Deforestation and forest degradation decreased forest structure and size that produce forest fragmentation. This study aimed to determine spatial distribution patterns and typology of forest fragmentation in the Labuhanbatu Selatan district. The study uses land cover image analysis, forest fragmentation analysis, correlation analysis, and typology analysis. Forest fragmentation is determined based on patch area (CA), patch density (PD), contiguity index (CONTIG), and proximity index (PROX). The study analyzes the correlation between variable factors and the degrees of forest fragmentation to develop a typology of fragmentation forest. The variables used to construct the typology of forest fragmentation are population density, productive age ratio, income, and slope. The classification of forest fragmentation has been completed to create a forest fragmentation typology. To determine the typology of forest fragmentation, the K-Means Cluster analysis method is used. Typology of forests fragmentation of Labuhanbatu Selatan district is three typologies. Typology 1 is the low forest fragmentation of Torgamba, Silangkitang, and Kota Pinang sub-district, typology 2 is moderate forest fragmentation are the Kampung Rakyat, and Typology 3 is high forest fragmentation of Sungai Kanan sub-district.